2021
DOI: 10.1111/phn.12864
|View full text |Cite
|
Sign up to set email alerts
|

Climate, Health, and Nursing Tool (CHANT): Initial survey results

Abstract: Recognition and understanding of climate change as a global health issue has increased over the past two decades; in fact, the Oxford Dictionary named "climate emergency" the word of the year in 2019. The urgency to move on a trajectory that addresses the causes of climate change within the next decade is emphasized by reports recently released by international organizations such as the Intergovernmental Panel on Climate Change and the World Health Organization (Masson-Delmotte et al., 2018; World Health Organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 8 publications
(9 reference statements)
0
28
0
Order By: Relevance
“…Moreover, the consistency and validity of the NEAT-es have indicated similar results to the creators of the NEAT [ 30 , 32 ]. Although no previous study has validated NEAT in other languages, the creation and validation of the original NEAT indicated a high consistency in matching the current findings regarding the sub-scales [ 31 , 37 ].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Moreover, the consistency and validity of the NEAT-es have indicated similar results to the creators of the NEAT [ 30 , 32 ]. Although no previous study has validated NEAT in other languages, the creation and validation of the original NEAT indicated a high consistency in matching the current findings regarding the sub-scales [ 31 , 37 ].…”
Section: Discussionmentioning
confidence: 75%
“…These results are relevant since the previous analysis of English-speaking nurses indicated that they are conscious of their significant impact on their daily work and have skills to mitigate them [ 30 , 32 ] and their insufficient knowledge about the questionnaire topics. Nonetheless, such results could not be compared since the NEAT is unavailable in other languages.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As recommended by Levac et al [ 26 ], the question we wish to answer through this exploratory review has been clearly articulated and focused. The question under study in this exploratory literature review is, “what are nurses’ perceptions relative to climate change?” This question is justified by the need to advance knowledge about nurses’ perceptions of climate change to better prepare them to tackle these climate issues [ 16 , 20 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nurses, who make up a significant portion of health professionals engaged in improving the health and well-being of individuals [ 15 - 17 ], have a critical role to play in responding to and reducing health issues stemming from climate change [ 18 ]. Because they benefit from a high degree of public trust [ 19 ], nurses can play a leadership role in the health sector both by increasing awareness of climate change as an important health issue and by spearheading action and advocacy in the fight against climate change [ 20 ]. In their daily work, nurses also have an advocacy role toward their patients experiencing the effects of climate change, especially those who are the most vulnerable.…”
Section: Introductionmentioning
confidence: 99%